2007
DOI: 10.1007/s10162-007-0071-1
|View full text |Cite
|
Sign up to set email alerts
|

An Electric Frequency-to-place Map for a Cochlear Implant Patient with Hearing in the Nonimplanted Ear

Abstract: The aim of this study was to relate the pitch of high-rate electrical stimulation delivered to individual cochlear implant electrodes to electrode insertion depth and insertion angle. The patient (CH1) was able to provide pitch matches between electric and acoustic stimulation because he had auditory thresholds in his nonimplanted ear ranging between 30 and 60 dB HL over the range, 250 Hz to 8 kHz. Electrode depth and insertion angle were measured from high-resolution computed tomography (CT) scans of the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
74
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 21 publications
15
74
3
1
Order By: Relevance
“…However, not all patients adapt to reduce this mismatch. Bimodal CI users are more likely to experience no changes in pitch or even a drop in pitch for all electrodes, exacerbating the mismatch (Reiss et al 2007(Reiss et al , 2011(Reiss et al , 2012a; consistent with this finding, several long-term studies also found electrode pitch to be mismatched to and lower than the frequency-toelectrode allocations (e.g., Blamey et al 1996;Dorman et al 2007). For bimodal CI users, it is possible that instead of or in addition to adapting pitch, the brain adapts BSI to increase fusion of interaurally mismatched inputs to effectively reduce the perception of mismatch.…”
Section: Introductionsupporting
confidence: 52%
“…However, not all patients adapt to reduce this mismatch. Bimodal CI users are more likely to experience no changes in pitch or even a drop in pitch for all electrodes, exacerbating the mismatch (Reiss et al 2007(Reiss et al , 2011(Reiss et al , 2012a; consistent with this finding, several long-term studies also found electrode pitch to be mismatched to and lower than the frequency-toelectrode allocations (e.g., Blamey et al 1996;Dorman et al 2007). For bimodal CI users, it is possible that instead of or in addition to adapting pitch, the brain adapts BSI to increase fusion of interaurally mismatched inputs to effectively reduce the perception of mismatch.…”
Section: Introductionsupporting
confidence: 52%
“…It is, however, still possible that apical fibers of passage are stimulated by the apical-most electrodes in intracochlear implants in humans. In fact, research on pitch-matching between acoustic and electric hearing suggests that the apical electrodes of the intracochlear electrode are matched to lower pitches than would be predicted based on tonotopic locations (e.g., Boex et al, 2006;Dorman et al, 2007). Thus, it is possible that the apical-most specialized temporal coding neurons proposed by Middlebrooks and Snyder can indeed be excited by apical stimulation of intracochlear electrodes.…”
Section: Introductionmentioning
confidence: 98%
“…Electrode arrays designed to position stimulating contacts near the modiolus appear to operate with lower current thresholds than previous devices that were located closer to the lateral wall of the scala tympani. [15][16][17] The charge units of maximum comfortable loudness level of the 2 groups were compared to determine whether an electrode dislocation was associated with higher stimulus charges.…”
Section: Discussionmentioning
confidence: 99%